2020
DOI: 10.33429/cjas.10219.1/6
|View full text |Cite
|
Sign up to set email alerts
|

Oil Price Shocks, Fuel Subsidies and Macroeconomic (In)stability in Nigeria

Abstract: This paper studies the macroeconomic implications of oil price shocks and the extant fuel subsidy regime for Nigeria. To do this, we develop and estimate a New-Keynesian DSGE model that accounts for pass-through effect of international oil price into the retail price of fuel. Our results show that oil price shocks generate significant and persistent impacts on output, accounting for about 22 percent of its variations up to the fourth year. Under our benchmark model (i.e. with fuel subsidies), we show that a ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 37 publications
(50 reference statements)
0
28
0
Order By: Relevance
“…Furthermore, the Buhari administration has been accused of poor intelligence gathering on the part of the law enforcement agency. This is attributed to the fact that the herdsmen-killers do return to communities where they had killed people and destroyed properties, yet nothing happens to them and they go with brute confidence even issuing threats to farmers who have reported their evil activities to the authorities (Omotosho, 2019). In the face of all these realities, the keen observers put forward a question what are the strategies deployed by the Buhari administration to contain the herders-farmers conflict and its impact on the economy of Nigeria.…”
Section: Buhari's Administration and The Herders-farmers Conflict In ...mentioning
confidence: 99%
“…Furthermore, the Buhari administration has been accused of poor intelligence gathering on the part of the law enforcement agency. This is attributed to the fact that the herdsmen-killers do return to communities where they had killed people and destroyed properties, yet nothing happens to them and they go with brute confidence even issuing threats to farmers who have reported their evil activities to the authorities (Omotosho, 2019). In the face of all these realities, the keen observers put forward a question what are the strategies deployed by the Buhari administration to contain the herders-farmers conflict and its impact on the economy of Nigeria.…”
Section: Buhari's Administration and The Herders-farmers Conflict In ...mentioning
confidence: 99%
“…Utilizing a New-Keynesian DSGE model to examine the macroeconomic implications of oil price shocks and the fuel subsidy regime in Nigeria, Omotosho (2019) discovered that oil price shocks impacted on headline inflation, though, the contribution was minimal owing to incomplete pass-through of international oil prices to domestic fuel price. The study revealed 85-113 that a negative oil price shock generated lower marginal cost and culminated in a fall in domestic inflation.…”
Section: -113mentioning
confidence: 99%
“…Similarly, the relationship between oil price declines and inflation is captured by β 6 , and is expected to also be positive, implying that decline in oil prices leads to lower marginal cost of production and a fall in inflation. However, falling oil prices weaken the foreign exchange earnings of oil exporting countries which are import dependent, manifesting in the depreciation of the domestic currency and resulting in rising import prices and increase in domestic inflation (See Bala & Chin, 2018;Omotosho, 2019). Consequently, β 6 can be negative in Nigeria.…”
Section: Model Specificationmentioning
confidence: 99%
“…Their results suggest that inflation in Nigeria is a monetary phenomenon, price stickiness is observed, and monetary policy reacts to exchange rate movement; while foreign inflation, external debt and exchange rate shocks are shown to drive output in Nigeria. More recently, Omotosho (2019) in an estimated new Keynesian DSGE model which features oil price passthrough and fuel subsidies, reports that a negative oil price shock reduces aggregate output, catalyses non-oil output, increases inflation and depreciates the exchange rate. The paper further shows that the severity of output contraction sequel to a negative oil price shock is amplified in a model with fuel subsidies but advise caution on the removal of fuel subsidies due to observed amplification of macroeconomic volatilities, resulting therefrom.…”
Section: Introductionmentioning
confidence: 99%